2021
DOI: 10.1111/ijcp.14055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patient safety culture in community pharmacies in Qatar

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Five studies [14][15][16]18,22 were conducted on pharmacists, whereas 6 studies (8 surveys) 17,[19][20][21]23,24 were carried out on all pharmacy staff members such as pharmacists, technicians, clerks, and pharmacy students on apprenticeship. Two studies (3 surveys) 17,18 originated from the United States, and the remainder were distributed as follows: Malaysia, 14 Kuwait, 15 United Arab Emirates, 16 Ethiopia, 19 Saudi Arabia, 20 Qatar, 21 Iraq, 22 Jordan, 23 and Singapore. 24 Eleven studies had response rates between 24.0% and 99.2%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies [14][15][16]18,22 were conducted on pharmacists, whereas 6 studies (8 surveys) 17,[19][20][21]23,24 were carried out on all pharmacy staff members such as pharmacists, technicians, clerks, and pharmacy students on apprenticeship. Two studies (3 surveys) 17,18 originated from the United States, and the remainder were distributed as follows: Malaysia, 14 Kuwait, 15 United Arab Emirates, 16 Ethiopia, 19 Saudi Arabia, 20 Qatar, 21 Iraq, 22 Jordan, 23 and Singapore. 24 Eleven studies had response rates between 24.0% and 99.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from Qatar 21 and Jordan 23 compared PRRs according to the type of pharmacy. The study from Qatar 21 classified the pharmacy type into 2 groups: chain pharmacy and independent pharmacy. The chain pharmacy group demonstrated higher PRRs for 7 items, including "this pharmacy is well organized," "staff work together as an effective team," and "technicians in this pharmacy receive the training they need to do their jobs."…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in Qatar, Saudi Arabia, and Sweden also found staffing to record low PPRs. [31][32][33] Brain drain is another factor contributing to the understaffing of Nigerian healthcare facilities. 34 A study showed that the National Health Service in the United Kingdom employs no fewer than 5405 Nigerian-trained medical professionals, 35 Federal and state governments can address the brain drain by resolving issues such as low wage compensation, poor infrastructure, limited educational opportunities, and poor working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Qatar, Saudi Arabia, and Sweden also found staffing to record low PPRs. 3133 Brain drain is another factor contributing to the understaffing of Nigerian healthcare facilities. 34 A study showed that the National Health Service in the United Kingdom employs no fewer than 5405 Nigerian-trained medical professionals, and according to the statistics in Britain, there are 137,000 foreign healthcare professionals representing 202 different nationalities collaborating with British healthcare workers, with 3.9% of them being Nigerian medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, community pharmacies have continuously attempted to improve the quality of health and pharmaceutical care services provided to patients, focusing on optimizing patient safety and decreasing unintended mistakes during healthcare delivery. Before the COVID-19 pandemic, several studies assessed patient safety culture in community pharmacy settings both internationally and regionally [ 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Previous research has identified organizational breakdown, insufficient staffing, increased production pressures, and provider fatigue as factors contributing to poor patient safety [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%